Próba identyfikacji specyfiki rynku FMCG w Polsce - Dziechciarz, Marta (An attempt to identify the particularities of Polish FMCG market, 2005)
The article describes the main factors influencing FMCG market in Poland. The discussion of retail and wholesale market trends is presented. The reasons for the popularity of private labels and the reasons for the significant growth of their shares in FMCG offer are identified. The particularities in Polish consumer behavior on FMCG market are described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 106-116